Identifying factors affecting the productivity of nursing service empirical research in Batool Teaching Hospital and the Hospital public of Baquba in Diyala province - عبد الوهاب نادية لطفي; عباس محمد زيد (Journal of Economics and Administrative Sciences, 2017)
This research aims to measure the productivity of nursing services and recognize the reality of providing such services in some public hospitals in the province of Diyala, as well as identify the most important factors affecting the productivity of nursing services, and developer measure adopted by the researcher (Kien, 2012), which includes seven factors (workforce , management team, stimulation, pressure of working hours (time), material / equipment, supervision, safety), Used the experimental method in the search, one of the private scientific research curriculum depends primarily on the scientific experiment and study of the subject, or a scientific phenomenon, which provides an opportunity to learn the facts through these experiences, for the purpose of measuring the factors affecting the productivity of nursing services, and research involved a sample of nurses working in hospitals (Virgin educational and Baquba educational year), and the sample was selected group of nurses, workers and nurses in providing nursing services for hospitals surveyed totaling (300), a nurse and a nurse form the equivalent of (100%) of them, for the purpose of measuring the factors affecting the productivity of nursing services, and research involved a sample of nurses working in hospitals ((Baquba General Teaching Hospital , and AL Batool Teaching Hospital), it has subjected measure of test validity and reliability, and used many of the statistical methods such as mean and standard deviation, test (T), and exploratory Kaiser - Meyer - Aolkin scale and test Bartlett which measures the correlation between variables as well as the U Mann Whitney test differences morale among the answers of nurses in the surveyed hospitals, using statistical software (SPSS), The research concluded inter conclusions Perhaps the most prominent of the authorized distribution for the preparation of nurses on different sections in these hospitals is appropriate to the needs of these sections, which led to the burden of high work on some nurses, especially in the consulting departments and emergency with the lack of appropriate incentives for nurses parallel tasks assigned to them, as well as for the wages granted to them is not equivalent to the effort by them, and there is no granted opportunities for them to develop their skills and complete their studies all contributed significantly to the lack of motivation to work, has recommended the search a number of recommendations including the need to take into account the needs of each department of the hospital nurses according to the number of patients who are in each section in order to distribute the workload evenly all the nurses in these hospitals, as well as a review of rewards and incentives granted to them and that the grant is in line with the seriousness of the work and its size within the surveyed hospitals.